2021
DOI: 10.3390/biom11121789
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Proteasome Enhancement by Small Molecules

Abstract: The proteasome system is a large and complex molecular machinery responsible for the degradation of misfolded, damaged, and redundant cellular proteins. When proteasome function is impaired, unwanted proteins accumulate, which can lead to several diseases including age-related and neurodegenerative diseases. Enhancing proteasome-mediated substrate degradation with small molecules may therefore be a valuable strategy for the treatment of various neurodegenerative diseases such as Parkinson’s, Alzheimer’s, and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 274 publications
(360 reference statements)
0
16
0
Order By: Relevance
“…The UPP is relevant in neural development and brain structure and also in maintenance of their functions, and is implicated in synaptic plasticity, formation, and maintenance of memory. Recently, it was found that the dysfunction of this proteasomal degradation pathway leads to changes in cell death by apoptosis in diverse cell types and may be implicated in the pathogenesis of several diseases, either through hypofunction, as in neurodegenerative diseases [ 61 , 62 ], or by hyperfunction, as in the case of neoplastic diseases [ 57 , 62 ]. More recently, ubiquitin system dysfunction has been implicated in chronic pain, mainly in neuropathic pain (NP) and inflammatory pain, through ubiquitination modified protein receptors and ion channels to affect synaptic activity and efficiency [ 57 ].…”
Section: Apoptosis Pathways As Mediators Of Pain Formationmentioning
confidence: 99%
“…The UPP is relevant in neural development and brain structure and also in maintenance of their functions, and is implicated in synaptic plasticity, formation, and maintenance of memory. Recently, it was found that the dysfunction of this proteasomal degradation pathway leads to changes in cell death by apoptosis in diverse cell types and may be implicated in the pathogenesis of several diseases, either through hypofunction, as in neurodegenerative diseases [ 61 , 62 ], or by hyperfunction, as in the case of neoplastic diseases [ 57 , 62 ]. More recently, ubiquitin system dysfunction has been implicated in chronic pain, mainly in neuropathic pain (NP) and inflammatory pain, through ubiquitination modified protein receptors and ion channels to affect synaptic activity and efficiency [ 57 ].…”
Section: Apoptosis Pathways As Mediators Of Pain Formationmentioning
confidence: 99%
“…It is increasingly accepted that proteasome activation may act protectively against the progression of various proteinopathies [ 25 , 65 ]. This is not surprising as diminished proteasome activity and reduced protein expression levels of various proteasome subunits have been detected in various in vitro and in vivo AD models, as well as in the brain samples of AD patients [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 7 The main protease of the UPS is the enzymatic core particle: the 20S proteasome. 3 , 4 , 7 , 8 The 20S proteasome is barrel-shaped and composed of four stacked heptameric rings where the two α-rings sandwich the two β-rings. 7 , 8 The β-rings house the three catalytic sites: the β 1 (caspase-like), β 2 (trypsin-like), and β 5 (chymotrypsin-like).…”
Section: Introductionmentioning
confidence: 99%
“…Proteostasis is a highly orchestrated balance between protein synthesis and degradation. , This process is regulated through the cross-coordination of several cellular pathways, including the ubiquitin–proteasome system (UPS). The UPS is a vital protein degradation system and is responsible for the degradation of most intracellular and soluble proteins. , The main protease of the UPS is the enzymatic core particle: the 20S proteasome. ,,, The 20S proteasome is barrel-shaped and composed of four stacked heptameric rings where the two α-rings sandwich the two β-rings. , The β-rings house the three catalytic sites: the β 1 (caspase-like), β 2 (trypsin-like), and β 5 (chymotrypsin-like). Access to these catalytic sites is controlled by the amino termini pendant groups of the α-rings that interlace to form a gate to the interior of the 20S core particle. Regulatory particles, like the 19S cap, can dock into pockets between the α-rings and induce an open-gate 20S conformation.…”
Section: Introductionmentioning
confidence: 99%